Packaging and storage effects on Listeria monocytogenes reduction and attachment on ready-to-eat meat snacks - Lobaton-Sulabo, April Shayne (Kansas State University, 2014)
A total of three studies were conducted to evaluate the effects of different packaging systems and storage times on reduction of Listeria monocytogenes on ready-to-eat meat snacks. Study 1 was conducted to determine the effects of four packaging systems [heat sealed (HS), heat sealed with oxygen scavenger (HSOS), nitrogen flushed with oxygen scavenger (NFOS), and vacuum (VAC)] and storage times (24, 48, and 72 h, and 14 and 30 d) on reduction of L. monocytogenes in turkey jerky in the presence or absence of sodium nitrite. Inclusion of sodium nitrite in turkey jerky did not affect (P>0.05) L. monocytogenes log reductions regardless of packaging type or storage time. After 14 d of storage in HSOS, NFOS, or VAC, and 48 or 72 h in HS, a reduction of >1.0 log CFU/cm² of L. monocytogenes was achieved. Processors could use HS in conjunction with 48 h of ambient storage and be in compliance with the United States Department of Agriculture Food Safety and Inspection Service Listeria Rule of post-lethality treatment in achieving at least 1 log reduction of L. monocytogenes. Study 2 was conducted to investigate attachment of L. monocytogenes to uncured and cured turkey jerky packaged in HS, HSOS, NFOS, or VAC using scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). The SEM examination showed that L. monocytogenes is capable of adhering to uncured or cured turkey jerky surfaces. Elemental maps from EDS analysis revealed that no element was unique or elevated at sites of L. monocytogenes attachment. Elemental composition showed the presence of elemental sulfur and could be an indication of the presence of sulfur-containing amino acids in turkey jerky. Finally, Study 3 evaluated the affects of two packaging types (HSOS and NFOS) and four ambient storage times (24, 48, and 72 h, and 14 d) on reduction of L. monocytogenes on five commercial RTE meats and poultry snacks (beef tenders, beef jerky, beef sausage sticks, pork jerky, and turkey sausage sticks). A mean reduction of >1.0 log CFU/cm² of L. monocytogenes was achieved on all products, regardless of packaging or storage time. Correlation analysis provided some indication that reduction of L. monocytogenes increased with fat content. However, the strength of linear correlation was not sufficient to account for the differences in log reduction in L. monocytogenes. In study 1, a holding time of 24, 48, or 72 h for HSOS or NFOS packaging of was not effective for reducing L. monocytogenes by at least 1 log on turkey jerky. In contrast, packaging beef tenders, beef jerky, beef sausage sticks, pork jerky, and turkey sausage sticks in HSOS or NFOS for at least 24 h ambient storage was sufficient to achieve at least 1 log reduction in L. monocytogenes population. Specific components such as sulfur-containing amino acids in turkey jerky might be contributing to <1 log reduction of L. monocytogenes population on turkey jerky after 24, 48, or 72 h of ambient storage. Overall, nitrite was not an effective ingredient to control L. monocytogenes in turkey jerky. However, packaging such as HS, HSOS, NFOS or VAC and at least 24 h holding time were effective hurdles for controlling L. monocytogenes at post-lethality.
Keywords: Listeria monocytogenes; Packaging; Ready-to-eat; Poultry; Meat; Food Science (0359)